Understanding compulsory schooling legislation: a formal model and implications for empirical analysis - Mark Gradstein; Moshe Justman (Institute for the Study of Labor (IZA), 2009)
We construct a simple model of compulsory schooling in which legislation and compliance are endogenously determined by individuals disciplined by social norms, optimizing their voting decisions and the school attendance of their children. The model provides a formal framework for interpreting empirical results on the effect of compulsory-schooling legislation (CSL) on enrollment. This sheds light on the use of CSL as an instrumental variable to identify the benefits of schooling, suggesting how the estimates it produces may be biased.
Keywords: I21; 330; Education; compulsory schooling; compliance norms; Schulrecht; Normbefolgung; Bildungsverhalten; Soziale Norm; Theorie